Defining Greek Narrative - Cairns, Douglas L. (Edinburgh Leventis Studies, 2014)
Title Page -- Copyright -- CONTENTS -- PREFACE -- NOTES ON CONTRIBUTORS -- 1 INTRODUCTION -- PART I DEFINING THE GREEK TRADITION -- 2 BEYOND AUERBACH: HOMERIC NARRATIVE AND THE EPIC OF GILGAMESH -- 3 HOMERIC BATTLE NARRATIVE AND THE ANCIENT NEAR EAST -- 4 NARRATIVE FOCUS AND ELUSIVE THOUGHT IN HOMER -- 5 STRUCTURE AS INTERPRETATION IN THE HOMERIC ODYSSEY -- PART II THE DEVELOPMENT OF THE GREEK TRADITION -- 6 EXEMPLARITY AND NARRATIVE IN THE GREEK TRADITION -- 7 'WHERE DO I BEGIN?': AN ODYSSEAN NARRATIVE STRATEGY AND ITS AFTERLIFE -- 8 SOME ANCIENT VIEWS ON NARRATIVE, ITS STRUCTURE AND WORKING -- 9 WHO, SAPPHO? -- 10 THE CREATIVE IMPACT OF THE OCCASION: PINDAR'S SONGS FOR THE EMMENIDS AND HORACE'S ODES 1.2 AND 4.2 -- 11 NARRATIVE ON THE GREEK TRAGIC STAGE -- 12 STOCK SITUATIONS, TOPOI AND THE GREEKNESS OF GREEK HISTORIOGRAPHY -- 13 HELIODORUS THE HELLENE -- PART III BEYOND GREECE -- 14 LIVY READING POLYBIUS: ADAPTING GREEK NARRATIVE TO ROMAN HISTORY -- 15 PAMELA AND PLATO: ANCIENT AND MODERN EPISTOLARY NARRATIVES -- 16 THE ANONYMOUS TRAVELLER IN EUROPEAN LITERATURE: A GREEK MEME? -- BIBLIOGRAPHY -- INDEX.